Hubungan Perubahan Anatomi dan Fisiologi Sistem Pencernaan Dengan Kejadian Mual Muntah Pada Ibu Hamil Trimester I Di TPMB Bdn. Pepi Herfianti Tahun 2025 - Sari, Nela Novita; Maifita, Yesi (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Pregnancy is a physiological process that occurs in women, characterized by anatomical and physiological changes in various body systems, including the digestive system. These changes are caused by hormonal influences, particularly progesterone and estrogen, which increase during pregnancy. This study aims to determine the relationship between anatomical and physiological changes in the digestive system and the incidence of nausea and vomiting in first-trimester pregnant women at the Pepi Herfianti Community Health Center in Sungai Sariak. This study used a quantitative research design with a cross-sectional approach. The subjects were all first-trimester pregnant women who visited the Pepi Herfianti Community Health Center in Sungai Sariak in 2025. A sample of 40 respondents was selected using a purposive sampling technique. Data collection was conducted using a questionnaire that measured anatomical and physiological changes and the intensity of nausea and vomiting in pregnant women. Data analysis was performed using the chi-square test to determine the relationship between anatomical and physiological changes in the digestive system and the incidence of nausea and vomiting. The results showed a significant association between anatomical and physiological changes in the digestive system and the incidence of nausea and vomiting in pregnant women in the first trimester (p = < 0.05) with p = 0.038. Pregnant women in the first trimester who experienced anatomical and physiological changes tended to have an increased frequency of nausea and vomiting compared to pregnant women who did not experience anatomical and physiological changes in the digestive system and nausea and vomiting. The conclusion is that there is a significant relationship between changes in the anatomy and physiology of the digestive system and the incidence of nausea and vomiting in first trimester pregnant women at TPBM Bdn. Pepi Herfianti, Amd. Keb Sungai Sariak.